The book of Isaiah : personal impressions of Isaiah Berlin - Hardy, Henry (Boydell Press ; in association with Wolfson College, 2009)
Isaiah Berlin was born a century ago. One of the most celebrated British thinkers of the twentieth century, he was a tireless champion of freedom and diversity against control and conformity. His generous, open vision of life is displayed with special imm.